2005
DOI: 10.2337/diabetes.54.11.3190
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Lipases and Defect of Lipolysis in Human Obesity

Abstract: The mobilization of fat stored in adipose tissue is mediated by hormone-sensitive lipase (HSL) and the recently characterized adipose triglyceride lipase (ATGL), yet their relative importance in lipolysis is unknown. We show that a novel potent inhibitor of HSL does not inhibit other lipases. The compound counteracted catecholamine-stimulated lipolysis in mouse adipocytes and had no effect on residual triglyceride hydrolysis and lipolysis in HSL-null mice. In human adipocytes, catecholamine-and natriuretic pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
247
4
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 326 publications
(289 citation statements)
references
References 52 publications
(58 reference statements)
25
247
4
13
Order By: Relevance
“…We have recently demonstrated that subcutaneous adipose tissue ATGL expression levels are strongly correlated to the levels of HSL [11]. Here, we confirm this finding by showing a high level of correlation between ATGL and HSL expression in omental adipose tissue as well, suggesting that the expression of the two lipases may be tightly co-regulated in humans.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We have recently demonstrated that subcutaneous adipose tissue ATGL expression levels are strongly correlated to the levels of HSL [11]. Here, we confirm this finding by showing a high level of correlation between ATGL and HSL expression in omental adipose tissue as well, suggesting that the expression of the two lipases may be tightly co-regulated in humans.…”
Section: Discussionsupporting
confidence: 87%
“…These data further support our hypothesis on the respective role of HSL and ATGL in human adipose tissue lipolysis [11]. Stimulation of the catecholamine and natriuretic peptide pathways leads to the protein kinase-A (PKA)-and cGMP-dependent kinase (PKG)-dependent phosphorylation of HSL and hydrolysis of triglycerides by the enzyme.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations